In vitro cytotoxicity of ethanolic extract of the leaf of Calotropis gigantea from Ie Jue Geothermal Area, Aceh-Indonesia, and its mouthwash formulation against dental pulp cells - Diana Setya Ningsih, Rinaldi Idroes, Boy M. Bachtiar, Khairan Khairan, Trina Ekawati Tallei, Muslem Muslem (Journal of Applied Pharmaceutical Science, 2022)
The ethanolic Calotropis gigantea leaf extract (ECGLE) from Ie Jue geothermal area, Aceh-Indonesia, and ECGLE-based mouthwash formulation has been prepared. The formulation was prepared with various extract concentrations ranging from 0 to 25% of ECGLE. Both the extract and formulation were evaluated for antibacterial and in vitro cytotoxic activity in order to determine their potential medicinal value in the oral cavity. Antibacterial tests were carried out against Gram-negative bacteria (Porphyromonas gingivalis), Gram-positive bacteria (Solobacterium moorei), and a mix of both Gram-negative and Gram-positive bacteria (P. gingivalis + S. moorei). The cytotoxic activity was evaluated against human dental pulp primary cells (hDPPC) by calorimetric assay using 3-(4,5-dimethylthiazol-2- yl)-2,5-diphenyltetrazolium bromide. All formulations passed the stability test with a pH of 5.35–5.92. Antibacterial activity testing revealed that the higher the ECGLE concentration, the more effective it is against bacteria. In comparison with other formulations, formulation-3 containing 3 gr of ECGLE demonstrated the highest activity. The minimum inhibitory concentration (MIC) value and % inhibition of formulation-3 against P. gingivalis, S. moorei, and a mix of both bacteria were 0.089, 0.075, and 0.083 µg/ml and 88.924%, 90.691%, and 89.72%, respectively. The cytotoxicity activities (IC50) for both ECGLE and a formulation containing ECGLE were 6.44 and 0.27 gr/ml, respectively. The ability of cells to undergo apoptosis showed a strong correlation between cell viability and the ECGLE extract (R2 = 0.973) as well as ECGLE-based mouthwash formulation (R2 = 0.897). The greater the concentration of ECGLE extract or ECGLE-based mouthwash formulation, the lower the viability of hDPPCs, but the greater the antibacterial activity.
Keywords: Calotropis gigantea extract, geothermal area, mouthwash formulation, cytotoxicity, antibacterial